Composição regional e tecidual da carcaça de cabritos naturalizados do Alto Camaquã de diferentes idades. - Martins, Luciane da Silva (2011)
Thirty eight (38) castrated male goats were used to evaluate carcass tissue and regional composition. Animals were raised under extensive range conditions, in two family units, in the 2nd sub-district of Palmas, Bagé, State of RS, Brazil, localized within the area known as Alto Camaquã Territory. Twenty (23) animals born during June/July 2008, and were slaughtered in June 2009, with approximately 11-12 months of age. Fifteen (15) animals born in March/April 2009 were slaughtered in December 2009, with approximately 8-9 months of age. Carcasses were separated longitudinally in two halves. Afterwards six cuts were obtained: foreleg, hind-leg fluctuating ribs, fixed ribs, neck and breast, each one being weighed, to calculate the proportion in relation to the corrected cold carcass weight. Different cuts obtained were frozen for later tissue evaluation. Foreleg and hind-leg were defrosted and dissect to determine muscle tissue composition, bone, subcutaneous fat, inter-muscular fat and other tissues. Each resulting tissue was weighed and its proportion calculated in relation to the corrected weight. Data were submitted to variance analysis (proc. GLM). Results demonstrated significant differences (P<0.05) between the age of slaughter in carcass regional components, whereas foreleg and hind-leg tissue composition did not differ significantly for the majority of the variables analyzed. However, 8-9 months goats showed greater relation for muscle:fat in foreleg compared to 11-12 months animals. Thus, naturalized goats of the Alto Camaquã Territory, grown extensively and slaughtered in December, or slaughtered in June with 11-12 months age, presented different tissue and regional composition in carcasses. Therefore, it is not recommended to include these two group types in a same meat brand (indication of quality) classification.